2014
DOI: 10.1155/2014/165818
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Psychiatric Disorders in Bariatric Surgery Candidates with the German Version of the Patient Health Questionnaire

Abstract: Objective. Obesity has been linked to psychiatric disorders in several studies. Prevalence and severity of psychiatric disorders are high in patients undergoing bariatric surgery. Thus, psychiatric assessment of bariatric surgery candidates has become a standard procedure. However, socially desirable responding leads to biased results in self-reported questionnaires. Here, bariatric surgery candidates were screened with the Patient Health Questionnaire (PHQ-D) additionally to the psychiatric examination. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…Although there is evidence of the higher prevalence of mood disorders in bariatric surgery patients [21] and and WV residents [13], a few similar examinations of psychological profiles of bariatric surgery patients indicated these minimal symptom classifications [25]. Previous studies examining screening of depressive disorders in preoperative bariatric patients indicated the socially desirable response bias as patients understand that the psychological screening is preemptive clearance prior to receiving surgery [37,38]. Attention to social desirability prior to surgery in an Appalachian cohort should be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is evidence of the higher prevalence of mood disorders in bariatric surgery patients [21] and and WV residents [13], a few similar examinations of psychological profiles of bariatric surgery patients indicated these minimal symptom classifications [25]. Previous studies examining screening of depressive disorders in preoperative bariatric patients indicated the socially desirable response bias as patients understand that the psychological screening is preemptive clearance prior to receiving surgery [37,38]. Attention to social desirability prior to surgery in an Appalachian cohort should be further explored.…”
Section: Discussionmentioning
confidence: 99%